Sebuah Laporan Kasus Seorang gadis berusia 13 tahun dengan Defek Septum Atrio-Ventrikular Lengkap (subtipe Intermediate) dan Blok AV Total - Alit Utamayasa, I Ketut; Nastiti, Prima Hari; Hidayat, Taufiq; Abdur Rahman, Mahrus (Universitas Muhammadiyah Surabaya, 2025)
Atrioventricular septal defects (AVSD) constitute a spectrum of anomalies caused by abnormal endocardial cushion defects. Many classifications have been used to describe AVSD. There is generally subclassified into complete and partial forms. Complete AVSD is characterized by a primum atrial septal defect (ASD) contiguous with an inlet ventricular septal defect (VSD) and a common AV valve. Intermediate AVSD is a subtype of complete AVSD that has distinct right and left atrioventricular valve orifices by a bridging tongue despite having only one common annulus. In some children or adults, we may see unoperated partial or intermediate AVSD, which may be asymptomatic or may present with congestive heart failure, exertional limitation, pulmonary hypertension, infective endocarditis, or heart rhythm disorder. In some cases of AVSD has atrioventricular (AV) conduction disorder, mostly on first-degree AV block. We report a case of a 13-year-old girl with complete AVSD (intermediate subtype) and pulmonary hypertension who is concomitant with total AV block. The patient has undergone implantation of a permanent pacemaker for total AV block and conservative therapy for complete AVSD. Anatomical assessment by trans-thoracal echocardiography (TTE) was essential for diagnostic and detailed morphological characterization of AVSD.